Les impacts de la guerre du Việt Nam sur les forêts d’A Lưới - Amélie Robert-Charmeteau (VertigO)
During the Việt Nam war, the Hồ Chí Minh trail crossed the present district of A Lưới (Thừa Thiên Huế province, central Việt Nam). Consequently, a great quantity of herbicides was sprayed and many bombs were dropped on this area. Forests were a prime target. These military practices have consequences on sylvosystems but they’re controversial. The purpose of this study is to objectively identify the impacts of the war on landscape dynamics. The method consists in a regressive diachronic analysis of landscapes. The iconographic sources (satellite images, aerial photographs) are favored because they’re a priori unbiased. The war is not the only studied period. Indeed, the environmental consequences of the military practices are analyzed in the short term as much in the long term, to know the impacts on current landscapes. Moreover we would like to test the hypothesis, that pre-and post-war practices have worsened the strict impact of the conflict. Landscape dynamics and human practices in A Lưới area are analyzed for each identified key period, from the colonization to today. The research was conducted in the framework of a PhD. It allows to conclude that the war is a factor of forest decline but not the only one; its marks on the current landscapes are only occasional.